Antioxidant activity of orange peel powder in ghee at accelerated temperature - Manjunatha, M; Sinha, Chitranayak; G, Mahesh Kumar; Kumari, Khushbu; BA, Anand; D, Vairat Amita (Indian Journal of Dairy Science, 2019)
Antioxidant potential of orange peel powder in ghee was demonstrated. Orange peel powder (1, 1.5 and 2%) was added in to butter and prepared ghee and stored for accelerated storage study at 60±2°C. Ghee with BHA (0.02%) and control (without any additives) were also prepared, stored and analyzed for comparison during the study. Peroxide value and thiobarbuturic acid (TBA) of ghee samples stored at accelerated condition (60°C±2) were analyzed at 4day interval during 16day storage period. Peroxide value and TBA were observed to increase in all the samples with highest in the control. Increase in peroxide value was least in the sample treated with 2% orange peel powder whereas the sample treated with BHA was observed with lowest increase in TBA value. Orange peel powder can be utilized as a source of natural antioxidant for reducing oxidative deterioration in ghee.